The almightier : how money became God, greed became virtue, and debt became sin - Vigna, Paul (St. Martin's Press, 2025)
"The complete story of how we came to worship money, and how we can stop greed from destroying everything. The pursuit of wealth is considered an essential function of human nature, and greed is an unspoken civic virtue. Many of us revere billionaires and Wall Street rain-makers, then complain about "the system" being rigged, and wonder why the country doesn't seem to work for the little guy anymore. Some blame the Deep State for income inequality and corruption, and others blame capitalism, but the truth is that these issues have much deeper roots: our devotion to money is a manmade invention that has transformed over thousands of years to replace religion as the foundation of our society, and it is tearing civilization apart. In The Almightier, journalist Paul Vigna uncovers the forgotten history of money, tracing the uneasy and often accidental alliance between wealth and religion as it developed from ancient city-states to today's secular world, where religious devotion has receded and greed has stepped in to fill the void. Through engaging anecdotes, original research, and fresh perspectives on the causes of the many challenges we face today, Vigna makes a compelling argument that money has no power apart from the power we give it. We can build a better future, where we don't need to choose between helping others and getting ahead. But we can't repair the damage that greed has done until we understand how it took over our world in the first place"-- Provided by publisher.